Developing and validating a questionnaire to measure attitude toward child adoption: A psychometric process - Masumeh Ghazanfarpour; Shirin Aminizadeh; Katayoun Alidousti; Mahlegha Dehghan; Atefeh Ahmadi (Wolters Kluwer Medknow Publications, 2023)
Background: Despite the mutual benefit of adoption, due to the adverse attitude related to the barriers perceived by the couples, some people are not interested in adoption. The purpose of this study was to develop and validate a questionnaire to measure attitudes toward child adoption. Materials and Methods: This secondary analysis is part of a larger study on 178 infertile couples referring to the Afzalipour Infertility Center in Kerman, Iran. Factor Analysis (FA) was performed. The sampling was conducted using the convenience sampling method. The questionnaire was implemented using a mixed-method approach in three phases. Firstly, a pool was created. The second phase involved content validity. Lastly, construct validity was conducted. Results: The final version of the questionnaire with 20 questions had a total Cronbach's alpha of 0.70%. Six factors with eigenvalues of higher than 1.00 were extracted, which accounted for 52% of the total variance. These factors were "spiritual-psychological status of the new parents," "psychological status of the adopted child," "undesirable behaviors of others in the future," "anxiety of the new parents," "physical-behavioral characteristics of the adopted child," and "socio-economic factors." The model extracted from the Exploratory Factor Analysis (EFA) was confirmed by Confirmatory Factor Analysis (CFA). The 6-factor structure adequately fitted the data (Comparative Fit Index (CFI) = 0.93; root mean square error of approximation [RMSEA] = 0.047; X2/df = 1.393; p = 0.002. Conclusions: The internal consistency and construct validity of the questionnaire were confirmed. This instrument can be used in clinical and research practices.